2021
DOI: 10.22146/jmpf.61343
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Disposal of Unused Medicines in Take-Back Programs

Abstract: Unused medicines in the household cause many problems. Medicines take-back programs were established to prevent inappropriate medicines disposal, abuse, accidental poisoning, and help reduce the number of unused medicines in households. A literature search using the keywords “unused AND medicine”, “disposal AND unused AND medicine”, “reasons AND medicine AND disposal”, “medicine AND take-back program” and “cost AND medicine AND take-back program” in PubMed, Science Direct, Scopus and Google Scholar. Articles p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…The economic value may have influenced the willingness to receive unused and expired household medications, as observed in previous studies ( El-Hamamsy, 2011 ; Perry, Shinn and Stanovich, 2014; Law et al, 2015 ; Moustarah, Desai and Blebea, 2020; Rahmadani and Kristina, 2021 ). Handling medication waste requires direct costs to properly dispose of the medication and avoid environmental issues ( West, et al, 2014 , Rahmadani and Kristina, 2021 , Romanelli and Lucente, 2022 ). Reportedly, healthcare facilities, particularly clinics and community health centers, often do not make specific budget allocations for handling unused or expired medications medications ( Nurfitria et al, 2022 ).…”
Section: Discussionmentioning
confidence: 72%
“…The economic value may have influenced the willingness to receive unused and expired household medications, as observed in previous studies ( El-Hamamsy, 2011 ; Perry, Shinn and Stanovich, 2014; Law et al, 2015 ; Moustarah, Desai and Blebea, 2020; Rahmadani and Kristina, 2021 ). Handling medication waste requires direct costs to properly dispose of the medication and avoid environmental issues ( West, et al, 2014 , Rahmadani and Kristina, 2021 , Romanelli and Lucente, 2022 ). Reportedly, healthcare facilities, particularly clinics and community health centers, often do not make specific budget allocations for handling unused or expired medications medications ( Nurfitria et al, 2022 ).…”
Section: Discussionmentioning
confidence: 72%
“…Because pharmacies are easily accessible to the community, the implementation of the drug return program is primarily done in them. According to the scoping review study, the number of drugs returned demonstrated the community's enthusiasm for participating in the program (Rahmadani & Kristina, 2021). This indicates that the drug return program could be a viable solution to the community's need for a specialised drug waste management program.…”
Section: Discussionmentioning
confidence: 99%